Authentic Assessment in Flexible Learning Modality and the Learning Outcomes in Readings in the Philippine History Among First-Year College Students - Habagat, John Bert A.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2024)
The research utilized a descriptive-correlational design. Descriptive design was used to describe the perception of the students. In order to gather the information in the study, In order to determine if there is significant relationship between authentic assessment strategies and tools and learning outcome, correlational research was used. It utilized quantitative approach of research in gathering the necessary data. The survey questionnaire was used to gather data and later on the score of the student after using the authentic assessment. The respondents of this study are twenty-four (24) first year college students from Bachelor of Science in Fisheries and Aquatic Resources and another thirty-two (32) first year college students from Bachelor of Science in Industrial Technology. A total of fifty (56) first year college students are the respondents of the study from Southern Luzon State University, Alabat Campus, Quezon. Each variable has seven statements describing respondents’ perceptions on the authentic assessment strategies and tools. The researcher used the weighted mean for the checklist questionnaire part I, II, and III. This study concluded the effectiveness of authentic assessment in flexible learning modality of readings in Philippine History for first year college students of SLSU Alabat, Quezon. Specifically, this study aimed to determine the perception of the respondents on the effectiveness of the developed authentic assessment in terms of: paper and pencil assessment; assessment strategy in communication; performance assessment; observation assessment; and, self-assessment. Also, this study aimed to know the perception of the respondents on the effectiveness of authentic assessment tools such as: checklist; rating scale; learning log; and anecdotal records.The study posited four hypotheses, one of which states that there is no significant relationship between the perception of the respondent on the developed authentic assessment and their level of learning outcomes in Readings in Philippine History. The second hypothesis states that there is a significant relationship between the perception of the respondent on the developed authentic assessment and their level of learning outcomes in Readings in Philippine History. While the third hypothesis states that there is no significant relationship between the perception of the teachers on authentic assessment tool and students’ level of learning outcomes in readings in the Philippine History. Finally, the fourth hypothesis states that that there is significant relationship between the perception of the teachers on authentic assessment tool and students’ level of learning outcomes in readings in the Philippine History